2021
DOI: 10.1021/acs.chemmater.1c03466
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Design of High-Quality Epitaxial Aurivillius Thin Films

Abstract: Efforts for the integration of ferroelectric materials in nonvolatile, low energy consuming memories have so far been focused on perovskite oxide materials. Their down-scaling for nanodevices is, however, hindered by finite-size effects, and alternative materials offering more robust polar properties are required. Layered ferroelectrics of the Aurivillius phase have since emerged as promising candidates with robust polarization at subunit-cell thicknesses. Their controlled growth in the epitaxial thin film for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Furthermore, from a practical point of view, common pressure sensors and gas flow controls are sensitive and precise enough to ensure almost continuous fine-tuning of Λ and c . In agreement with our findings, Gradauskaite et al recently reported on stabilizing layer-by-layer growth modes in PLD for Bi m +1 Fe m –3 Ti 3 O 3 m +3 Aurivillius phase thin films and were able to adjust m from 4 up to 8 by increasing the laser fluence and background pressure …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, from a practical point of view, common pressure sensors and gas flow controls are sensitive and precise enough to ensure almost continuous fine-tuning of Λ and c . In agreement with our findings, Gradauskaite et al recently reported on stabilizing layer-by-layer growth modes in PLD for Bi m +1 Fe m –3 Ti 3 O 3 m +3 Aurivillius phase thin films and were able to adjust m from 4 up to 8 by increasing the laser fluence and background pressure …”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, from a practical point of view, common pressure sensors and gas flow controls are sensitive and precise enough to ensure almost continuous fine-tuning of Λ and c. In agreement with our findings, Gradauskaite et al recently reported on stabilizing layer-by-layer growth modes in PLD for Bi m+1 Fe m−3 Ti 3 O 3m+3 Aurivillius phase thin films and were able to adjust m from 4 up to 8 by increasing the laser fluence and background pressure. 19 Keeping in perspective the aforementioned analysis, we are now in a position to address the underlying reasons for the observed dependencies, that is, which physical processes are adjusted when tuning these process parameters? It is known that the formation of oxide nanostructures can be governed by diffusion-limited processes during the growth.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Note that the lateral PFM shows a maximum response when the cantilever lies perpendicular to the polar axis of the film. 24 The film grown on LSMO/STO(110) shows similar vertical and in-plane contrasts (Fig. 1d and e).…”
Section: Resultsmentioning
confidence: 66%
“…Let us now investigate OPB formation in our ultrathin BFTO n = 4 films. The films of the Aurivillius phase are grown using PLD with reflection high-energy electron diffraction (RHEED) monitoring to ensure the subunit-cell thickness accuracy. , The excellent epitaxial lattice matching between the BFTO and NGO (001) (henceforth crystallographic indices correspond to the orthorhombic u.c. notation) substrate results in films that are single-crystalline and uniaxially polarized along the [010] substrate direction ( a -axis of BFTO). , We use APT to image a 5-u.c.-thick BFTO film.…”
mentioning
confidence: 99%
“…The films of the Aurivillius phase are grown using PLD with reflection high-energy electron diffraction (RHEED) monitoring to ensure the subunit-cell thickness accuracy. , The excellent epitaxial lattice matching between the BFTO and NGO (001) (henceforth crystallographic indices correspond to the orthorhombic u.c. notation) substrate results in films that are single-crystalline and uniaxially polarized along the [010] substrate direction ( a -axis of BFTO). , We use APT to image a 5-u.c.-thick BFTO film. The APT measurement allows three-dimensional reconstruction of the chemical composition on the atomic length scale and helps locating structural defects and their propagation within the volume .…”
mentioning
confidence: 99%